Features of Risk Factors for Patients with Low Back Pain Among Cirebon City Secretarial Staff - Moh. Irwan Dharmansyah; Helga Marwa Afifah; Rian Damayanti; Muhammad Suhanda; Afifa Khairinnisa (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
Low Back Pain (LBP) refers to lower back pain that originates from the lower back region's spine, muscles, nerves, or other surrounding body parts. World Health Organization (WHO) statistics indicate that 619 million individuals suffered from low back pain in 2020, and that number is expected to rise to 843 million instances by 2030. Low back pain is a medical condition that can arise in a variety of occupations. Risk factors for LBP include smoking, obesity, poor posture, ergonomics, and high levels of physical stress at work. The aim of this study was to examine the risk factors in LBP patients. The method used in this research was descriptive with total sampling, the risk factors assessed included the parameters of age, sitting position, sitting duration, exercise frequency, body mass index. The results of the study were obtained in 39 low back pain The findings showed that most of the respondents were in their early adult years (50.0%), that they sat for long periods of time (24 employees, 61.5%), that they exercised occasionally (27 employees, 69.2%), and that they sat upright most of the time (26 employees, 66.7%). The Cirebon City Regional Secretariat has seven employees (17.9%) in the overweight category, eight employees (20.5%) in the obese category, and nine employees (23.1%) in the obesity category. In conclusion, 39 employees with low back pain engage in sitting activities that are typically prolonged (24 employees, or 61.5%), exercise frequently (27 employees, or 69.2%), and sit primarily upright (26 employees, or 66.7%). Additionally, 7 employees (17.9%) have an overweight BMI, 8 employees (20.5%) have an obesity BMI, and 9 employees (23.1%) have an obesity 2 BMI.